PENYIMPANGAN PARTISIPASI MASYARAKAT DALAM PENATAAN KAWASAN CAGAR BUDAYA - Budi Kurniawan (Jurnal Penelitian Humaniora, 2021)
In preserving cultural heritage based on community participation, the community engangement and their support greatly influence the outcome. This study aims to examine community participation in the activities of structuring cultural heritage carried out through the mechanism of subsidies. We employ research method using a case study approach to gain an in-depth understanding of the form and the influence of community participation in each stage of the preservation program and the factors that influence it. Based on the study, we found that there was a form of deviation of community participation, both in the implementation stage and in the post-activity utilization stage. The deviations in participation occur as a result of a mismatch between the objectives of the activity and the actual needs of the community. As for the factors that influence the occurrence of irregularities in community participation, the come from the internal form of motivation, commitment and attitude, as well as external factors in the form of activity management, and policy aspects.